Genome‐Wide Search for Nonadditive Allele Effects Identifies PSKH2 as Involved in the Variability of Factor V Activity - Blandine Gendre; Angel Martinez‐Perez; Marcus E. Kleber; Astrid van Hylckama Vlieg; Anne Boland; Robert Olaso; Marine Germain; Gaëlle Munsch; Angela Patricia Moissl; Pierre Suchon; Juan Carlos Souto; José Manuel Soria; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Factor V (FV) is a key molecular player in the coagulation cascade. FV plasma levels have been associated with several human diseases, including thrombosis, bleeding, and diabetic complications. So far, 2 genes have been robustly found through genome‐wide association analyses to contribute to the inter‐individual variability of plasma FV levels: structural F5 gene and PLXDC2. Methods and Results The authors used the underestimated Brown‐Forsythe methodology implemented in the QuickTest software to search for non‐additive genetic effects that could contribute to the inter‐individual variability of FV plasma activity. QUICKTEST was applied to 4 independent genome‐wide association studies studies (LURIC [Ludwigshafen RIsk and Cardiovascular Health Study], MARTHA [Marseille Thrombosis Association], MEGA [Multiple Environmental and Genetic Assessment], and RETROVE [Riesgo de Enfermedad Tromboembolica Venosa]) totaling 4505 participants of European ancestry with measured FV plasma levels. Results obtained in the 4 cohorts were meta‐analyzed using a fixed‐effect model. Additional analyses involved exploring haplotype and gene×gene interactions in downstream investigations. A genome‐wide significant signal at the PSKH2 locus on chr8q21.3 with lead variant rs75463553 with no evidence for heterogeneity across cohorts was observed (P=0.518). Although rs75463553 did not show an association with mean FV levels (P=0.49), it demonstrated a robust significant (P=3.38x10−9) association with the variance of FV plasma levels. Further analyses confirmed the reported association of PSKH2 with neutrophil biology and revealed that rs75463553 likely interacts with two loci, GRIN2A and POM121L12, known for their involvement in smoking biology. Conclusions This comprehensive approach identifies the role of PSKH2 as a novel molecular player in the genetic regulation of FV, shedding light on the contribution of neutrophils to FV biology.